2010
DOI: 10.1021/es103000v
|View full text |Cite
|
Sign up to set email alerts
|

Dioxins in Primary Kaolin and Secondary Kaolinitic Clays

Abstract: Since 1996 dioxins have been repeatedly detected worldwide in Tertiary ball clays used as anticaking agent in the production of animal feed and a variety of other applications. The dioxins of these natural clays are very unlikely of anthropogenic source, but no model of dioxin enrichment has been established. A hypothetical model is presented which explains the highly variable dioxin loadings of the Tertiary kaolinitic clays by natural addition during clay-sedimentation. To prove this hypothesis, Tertiary prim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 18 publications
1
18
0
Order By: Relevance
“…PCDFs were not detected or were found at the ultra trace level in the samples. These results were very similar to previous studies that reported PCDD/Fs in kaolinitic clays were characterized by congener profiles dominated by OCDD and HpCDDs and trace levels of PCDFs [1,2,5,13].…”
Section: Congener Profiles Of Pcdd/fs In the Test Piecessupporting
confidence: 92%
See 1 more Smart Citation
“…PCDFs were not detected or were found at the ultra trace level in the samples. These results were very similar to previous studies that reported PCDD/Fs in kaolinitic clays were characterized by congener profiles dominated by OCDD and HpCDDs and trace levels of PCDFs [1,2,5,13].…”
Section: Congener Profiles Of Pcdd/fs In the Test Piecessupporting
confidence: 92%
“…Schmitz et al [5] collected and analyzed Tertiary primary nonsedimentary kaolin and sedimentary kaolinitic clays in Europe. The results showed that the PCDD concentrations were in the range of 3-91 pg/g, 711-45,935 pg/g, and 13,513-1,191,120 pg/g, in primary kaolin, secondary kaolinitic clay, and lignitic clays, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The two notable land-uses are rice paddy soils in Japan impacted by contaminated pesticides (mainly PCP and CNP) (Kiguchi et al, 2007) and deep kaolinitic and lignitic clays from the US and Europe (Ferrario et al, 2000;Gadomski et al, 2004;Schmitz et al, 2011). Here we used PCA to compare the PCDD/F profiles in surface soil and deep soil layers among these studies to establish whether a common source was likely.…”
Section: Resultsmentioning
confidence: 99%
“…Preferential removal of lateral (2,3,7,8-substituted) profiles for tetra-to hepta-PCDDs (normalised to homologue totals) to compare global soils with similar OCDD-dominated PCDD/F profiles. Kaolinitic/lignitic clays (circles) are sourced from (Prange, 2003;Gadomski et al, 2004;Schmitz et al, 2011); rice paddy soils (squares) from Kiguchi et al (2007); Queensland agricultural, urban and industrial surface soils (triangles) from (Gaus et al, 2001;Prange, 2003;Müller et al, 2004;Gaus et al, 2009;Grant et al, 2011). Isomer groups for PCA (B) are defined in Table S4-SI, and groups that include 1,4,6,9-substituted isomers are highlighted in the loading plot (B) in blue.…”
Section: Pcdd/f Distributions In Soil Coresmentioning
confidence: 99%
See 1 more Smart Citation